Potential Expansion of Root Chicory Cultivation Areas in Chile - Donna Cortez; Manuel Paneque; Celián Román-Figueroa (Agronomy, 2025)
Root chicory (Cichorium intybus var. sativum) is a major source of inulin, a fiber with many dietary and medicinal uses. Chile is the only country outside Europe that produces inulin and is the third largest exporter worldwide. Root chicory cultivation has increased by 242% in Chile since 2006, highlighting its potential for expansion into new territories. In this study, land suitability (without restriction, mild restriction, moderate restriction, and unsuitable) for root chicory cultivation and its potential productivity were determined using Geographic Information System (GIS) and analytical hierarchy process (AHP). The regions where root chicory is currently produced (between the Maule and La Araucanía regions) showed the best suitability, as did the Valparaíso and O’Higgins regions. The potential maximum productivity ranged from 20 to 27 t DW ha−1, mainly concentrated in the Los Lagos region, despite the absence of land without restriction. This could be attributed to the high water availability in this region, which is consistent with the expected displacement of crop areas due to climate change. Field studies in the Los Lagos region are recommended to evaluate the feasibility of expanding root chicory cultivation in these areas.